The Importance Of Preventive Measures In Higher Education In The Legal Education System - Ibragimov Shukhrat Israilovich (Global Scientific Publishing, 2025)
The importance of preventive measures in the legal education system in higher education institutions is of great importance in the formation of legal awareness among students and their preparation for social responsibility in society. Preventive measures can prevent violations, develop legal culture among students, and eliminate negative behaviors. This, in turn, increases the quality of the educational process and strengthens justice, discipline, and the effectiveness of the legal system in society
Keywords: Preventive measures; legal education; crime